Low Proportion of Linezolid and Daptomycin Resistance Among Bloodborne Vancomycin-Resistant Enterococcus faecium and Methicillin-Resistant Staphylococcus aureus Infections in Europe - Markwart, Robby; Willrich, Niklas; Eckmanns, Tim; Werner, Guido; Ayobami, Olaniyi (Frontiers in Microbiology, 2021)
Vancomycin-resistant E. faecium (VREF) and methicillin-resistant S. aureus (MRSA) are associated with significant health burden. We investigated linezolid and daptomycin resistance among VREF and MRSA in the EU/EEA between 2014 and 2018. Descriptive statistics and multivariable logistic regression were used to analyze 6949 VREF and 35,131 MRSA blood isolates from patients with bloodstream infection. The population-weighted mean proportion of linezolid resistance in VREF and MRSA between 2014 and 2018 was 1.6% (95% CI 1.33-2.03%) and 0.28% (95% CI 0.32-0.38%), respectively. Daptomycin resistance in MRSA isolates was similarly low (1.1% [95% CI 0.75-1.6%). On the European level, there was no temporal change of daptomycin and linezolid resistance in MRSA and VREF. Multivariable regression analyses show that there was a higher likelihood of linezolid and daptomycin resistance in MRSA (aOR: 2.74, p < 0.001; aOR: 2.25, p < 0.001) and linezolid in VREF (aOR: 1.99, p < 0.001) compared to their sensitive isolates. The low proportion of linezolid and daptomycin resistance in VREF and MRSA suggests that these last-resort antibiotics remains effective and will continue to play an important role in the clinical management of these infections in Europe. However, regional and national efforts to contain antimicrobial resistance should continue to monitor the trend through strengthened surveillance that includes genomic surveillance for early warning and action.